A New Submersion Detection Sensor Using Two Resistance Temperature Detectors Operating on the Thermal Equilibrium Principle - Youngjun Lee; Young Sam Lee (Sensors, 2019)
In this study, a new submersion detection sensor with improved reliability and stability is proposed. The new sensor uses two Resistance Temperature Detectors (RTDs) and operates on the thermal equilibrium principle. The submersion detection sensor controls two RTDs that maintain a constant temperature difference between them in the surrounding environment. The first RTD is used as a reference sensor to measure ambient temperature and the second RTD is supplied with higher current than the reference sensor for self-heating. When submerged, because the thermal conductivity and convective heat transfer coefficient of water are higher than that of air, the temperature difference between the two RTDs is lower in water than in air based on the thermal equilibrium principle. Under these conditions, a submersion detector with a signal conditioning circuit detects these temperature differences. The static performance of the proposed sensor was evaluated by checking whether malfunctions occurred at varying ambient temperatures, differing humidities, and when there was rainfall. In addition, the dynamic performance was evaluated using the response time at varying ambient air temperatures before submersion and with changing water temperatures after submersion, as a metric. The proposed submersion detection sensor is expected to find useful application in aircrafts, ships, and various other industrial fields.